Cymbopleura deqinensis sp. nov. (Cymbellaceae; Bacillariophyceae), a new species from Yunnan Province, China - Meng, Wen-Wen; Guo, Ji-Shu; Zhang, Yu; Patrick Kociolek, John; Li, Yan-Ling (Phytotaxa, 2022)
Cymbopleura deqinensis sp. nov. was found in surface sediments of a small, oligotrophic high-mountain lake in Deqin County, Yunnan Province, Southwest China. We describe the morphology of this new species using light and scanning electron microscopy. Cymbopleura deqinensis sp. nov. has the morphological characteristics that are typical for the genus, including dorsally deflected external distal raphe ends and often ventrally deflected proximal raphe ends as well as lacking stigmata and apical pore fields. The new species is most similar to C. similiformis var. angusta and shares features with some other species in this genus, as well. Due to the apices being bent in opposite directions, giving the valves the appearance of being slightly sigmoid, this species may, also due to its small size and finer striation, be compared to species in the genus Encyonopsis. However, a unique set of characteristics sets C. deqinensis sp. nov. apart as a new species: 1) valve ends bend in opposite directions, 2) the shape of areolae are mostly round to elliptical, partly T-shaped, V-shaped or irregularly-shaped externally and round internally, 3) it has several larger areolae near the central area, 4) the shape of central area is rectangular to elliptical or occasionally not well expressed, with irregularly shortened striae. Brief notes on the associated diatom flora and its ecology are provided.